The Roles of Kinesthetic Perception, Adaptation, and Agility in the Football Skills of Football School Students in Bandung City - Hendrayana, Yudy (SIPATAHOENAN, 2015)
ABSTRACT: Great attention to football is not only paid by adults, but also children. For children, football has even been their part of life; in other words, their world is incomplete without football. This condition shows that football, as a sport game, has been an important aspect among children. Childrenâs great interest in football has encouraged football lovers to help channel the interest by founding the Football Schools, or famous by the abbreviation of SSB (Sekolah Sepak Bola) in Indonesian context. The purpose of this research is to study the contribution of kinesthetic perception, adaptation, and agility to football skills. This research was conducted at the Football Schools in Bandung with a sample of 40 students selected randomly. The research has found that there were positive correlations between: (1) kinesthetic perception and football skills; (2) adaptation and football skills; (3) agility and football skills; and (4) kinesthetic perception, adaptation, and agility with football skills. The findings give an implication that football skills can be increased by improving kinesthetic perception, adaptation, and agility.KEY WORD: Football schools in Bandung, students, kinesthetic perception, adaptation, agility, football skills, and positive correlations.INTISARI: âPeranan Persepsi Kinestetik, Adaptasi, dan Kelincahan terhadap Keterampilan Sepakbola pada Siswa-siwa Sekolah Sepakbola di Kota Bandungâ. Besarnya perhatian terhadap sepakbola tidak hanya dimiliki oleh orang-orang dewasa, tetapi juga anak-anak.Â  Bahkan bagi anak-anak, sepakbola telah menjadi bagian dari hidupnya; dengan kata lain, tidak ada dunia lain tanpa melakukan sepakbola. Keadaan ini menunjukkan bahwa sepakbola, sebagai olahraga permainan, telah menjadi agenda penting bagi kalangan anak-anak. Besarnya perhatian anak-anak terhadap sepakbola mendorong pencinta sepakbola untuk membantu menyalurkan keinginan tersebut dengan cara mendirikan Sekolah-sekolah Sepakbola, atau yang terkenal dengan singkatan SSB (Sekolah Sepak Bola) dalam konteks Indonesia. Tujuan dari penelitian ini adalah untuk mempelajari kontribusi persepsi kinestetik, adaptasi, dan kelincahan untuk keterampilan sepakbola. Penelitian ini dilakukan di Sekolah-sekolah Sepakbola di Bandung dengan sampel 40 siswa yang dipilih secara acak. Penelitian telah menemukan bahwa ada korelasi positif antara: (1) persepsi kinestetik dan keterampilan bermain sepakbola; (2) adaptasi dan keterampilan bermain sepakbola; (3) kelincahan dan keterampilan bermain sepakbola; serta (4) persepsi kinestetik, adaptasi, dan kelincahan dengan keterampilan bermain sepakbola. Temuan memberikan implikasi bahwa keterampilan bermain sepakbola dapat ditingkatkan dengan memperbaiki persepsi kinestetik, adaptasi, dan kelincahan.KATA KUNCI: Sekolah sepakbola di Bandung, siswa-siswa, persepsi kinestetik, adaptasi, kelincahan, keterampilan sepakbola, dan korelasi positif.About the Author: Dr. Yudy Hendrayana is a Senior Lecturer at the Faculty of Sports and Health Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. For academic interests, the author is able to be searched at: yudy_h2000@yahoo.comHow to cite this article? Hendrayana, Yudy. (2015). âThe Roles of Kinesthetic Perception, Adaptation, and Agility in the Football Skills of Football School Students in Bandung Cityâ in SIPATAHOENAN: South-East Asian Journal for Youth, Sports & Health Education, Vol.1(1) April, pp.85-98. Bandung, Indonesia: Minda Masagi Press, APAKSI Bandung, and KEMENPORA RI Jakarta, ISSN 2407-7348. Â Chronicle of the article: Accepted (March 2, 2015); Revised (March 24, 2015); and Published (April 21, 2015).